Nordic-Iberian Cod Value Chains: Explaining salted fish trade patterns - Lindkvist, Knut Bjørn (Springer, 2015)
This book is a multidisciplinary analysis of cultural, regional and economic factors affecting international food trade. Contributions from expert authors illuminate the importance of food culture prevailing in the market as a basis for decisions about food trading. Central concepts include value chains, conventions and public infrastructure and their importance for international trade.